Combined adaptive feedback and feedforward compensation for active vibration control using Youla–Kučera parametrization. (10th November 2018) - Airimitoaie, Tudor-Bogdan; Landau, Ioan Doré
Abstract: The combination of adaptive feedforward with adaptive feedback disturbance compensation has been suggested since a number of years as a potential solution for improving the performance of active vibration control systems. Unfortunately, as shown in the present paper there is a strong coupling between adaptive feedback and adaptive feedforward which may lead to instabilities and new algorithms which take into account this interaction are proposed in the paper. These algorithms take advantage of the Youla-Kučera parametrization of the feedback controller and feedforward compensator. First, the adaptive feedback algorithm is presented alone. Then, the adaptive feedforward algorithm is designed taking into account the feedback controller's presence in the loop. Stability of the complete scheme is obtained by appropriately filtering the regressor vectors in order to take into account a strictly positive real condition. Experimental results obtained on a relevant test-bench illustrate the performance of this approach to active vibration control. Comparison with adaptive feedback alone, with adaptive feedforward alone and adaptive feedforward + fixed feedback are provided.